2014
DOI: 10.1016/j.burns.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Up-to-date approach to manage keloids and hypertrophic scars: A useful guide

Abstract: Keloids and hypertrophic scars occur anywhere from 30 to 90% of patients, and are characterized by pathologically excessive dermal fibrosis and aberrant wound healing. Both entities have different clinical and histochemical characteristics, and unfortunately still represent a great challenge for clinicians due to lack of efficacious treatments. Current advances in molecular biology and genetics reveal new preventive and therapeutical options which represent a hope to manage this highly prevalent, chronic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
322
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(334 citation statements)
references
References 105 publications
(156 reference statements)
3
322
0
9
Order By: Relevance
“…Simman et al, also found that there was a proliferation of keloid fibroblasts in vitro after three weeks period and suggest that this agent might be in clinical trial post-keloid surgical excision. 36 Based on this in vitro study, a clinical trial was conducted by Bailey et al, on a group of 10 patients who received 1 mg ML of MMC topically for 3 min post-shaving removal of keloid scar with a repeated dose after three weeks. The patients follow up was every 2 months for 6 months and the keloid scar was photographed; pre-and post-treatment photos were assessed by two dermatologists who were not involved in the study.…”
Section: Mitomycin Cmentioning
confidence: 99%
“…Simman et al, also found that there was a proliferation of keloid fibroblasts in vitro after three weeks period and suggest that this agent might be in clinical trial post-keloid surgical excision. 36 Based on this in vitro study, a clinical trial was conducted by Bailey et al, on a group of 10 patients who received 1 mg ML of MMC topically for 3 min post-shaving removal of keloid scar with a repeated dose after three weeks. The patients follow up was every 2 months for 6 months and the keloid scar was photographed; pre-and post-treatment photos were assessed by two dermatologists who were not involved in the study.…”
Section: Mitomycin Cmentioning
confidence: 99%
“…The association between different techniques seems to be the only chance to treat keloids and reduce recurrence rate [15] , furthermore surgery is frequently the only opportunity to restore the correct anatomy distorted by the scar. …”
Section: Discussionmentioning
confidence: 99%
“…There is controversy not only regarding the presence of myofibroblasts in keloid tissues [2,4,8,44] but also regarding the conversion of fibroblasts into myofibroblasts by Gal-1 [24,26,45]; therefore, we sought to determine by double-immunofluorescence staining whether α-SM actin, the most common marker for myofibroblasts identification [46], was present in the fibroblasts of keloid tissues examined. Immunolocalization demonstrated that α-SM actin was completely absent in the fibroblasts expressing Gal-1 as well as in those that did not it (Fig.…”
Section: In Vivo Gal-1 Immunolocalizationmentioning
confidence: 99%
“…frequently occur on the anterior portion of the chest, shoulders, upper back, arms, cheeks and earlobes [1,2,[5][6][7][8][9][10]. Histopathologically, keloids are defined as inflammatory disorders characterized by exhibiting a thickened dermis containing numerous fibroblasts, abnormal vascularization, increased inflammatory immune cells, abundant hyalinised collagen bundles (keloidal collagen) and extracellular matrix (ECM) components including collagen, elastin, fibronectin and proteoglycans such as syndecan and versican, mainly produced by activated fibroblasts [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation